1p and/or 19q polysomy is an adverse prognostic factor in oligodendrogliomas, and easy to detect by automated FISH - Karine Michaud; Peter Vincent Gould; Myreille D’Astous; Claudie Paquet; Stephan Saikali (PLoS ONE, 2025)
Objective To study the feasibility of automated analysis by FISH technique in the determination of the 1p and/or 19q polysomy in oligodendrogliomas (OGs) and to explore its prognostic value. Methods We analyzed a retrospective monocentric series of 145 consecutive OGs with IDH mutation and 1p/19q codeletion. For all cases, automated FISH analyses were performed to determine 1p and/or 19q polysomy status and results were compared to manual analysis to verify the concordance of the two methods. Polysomic status was then compared to clinical and histological data, the CDKN2A deletion status when available, event free survival (EFS) and overall survival (OS). Results Our study comprised 79 grade 2 OGs (O2) and 66 grade 3 OGs (O3). Polysomy of 1p and/or 19q was observed in 58 cases (40% of whole cohort) with a significant enrichment in the high grade cohort (59% versus 24%; p < 0,0001) and recurrent cases (55%). A majority of polysomic cases were copolysomic for 1p and 19q (75% of the polysomic cohort) rather than 1p or 19q single polysomy (21% and 4% respectively). Polysomy was correlated to high grade histological criteria of high mitotic and Mib1 proliferative indices (p = 0,002 and p = 0,0005 respectively) and to vascular proliferation (p = 0,0003). Univariate and multivariate analysis showed a significant correlation betwen polysomy and a shorter EFS and OS (p = 0,02 and p = 0,016 respectively). Concordance between manual and automated analysis was almost perfect for both 1p and 19q analysis (96 and 98% respectively, κ = 0,92 and 0,95 respectively). Automated analysis revealed that the large majority of polysomic signatures are represented by a small number of R/G signals (mainly 7 signatures) allowing a very easy implementation to pre-existent FISH platforms analysis software. Conclusion 1p and/ or 19q polysomy status represent a prognostic factor in OGs and can be easily determined by automated analysis. Our study supports the clinical interest to determine the polysomic status in all primitive or recurrent OGs and underline the benefits of automated analysis which offers a better archive storage and facilitates multicentric comparison.